NT-proBNP for heart failure diagnosis in Primary Care: Costs or savings? A budget impact study - Fonseca, Cândida; Bettencourt, Paulo; Brito, Dulce; Febra, Helena; Pereira, Álvaro; Genovez, Victória; Lopes, Nelson (Revista portuguesa de cardiologia, 2022)
Chronic heart failure (CHF) is a growing public health concern and diagnosis can be challenging, particularly in primary care. This study aims to estimate the budgetary impact of introducing N-terminal pro-B-type natriuretic peptide (NT-proBNP) for CHF diagnosis in a primary care setting from the perspective of the Portuguese health system. A budget impact analysis was conducted over one-year from the patients’ first presentation. The standard of care (SoC) was compared to NT-proBNP at the point-of-care (PoC) or laboratory (Lab). A decision tree model was used to estimate the downstream costs associated with each of the three pathways. An estimated 81 012 patients were expected to present to primary care with new onset CHF symptoms. The use of NT-proBNP as a primary diagnostic tool is estimated to generate annualized savings of EUR 935 657 and EUR 2 982 443 in the Lab and PoC setting, respectively. Estimated cost savings were due to the need for fewer medical visits, hospitalizations and echocardiograms (ECHO). The Lab and PoC settings led to similar reductions in hospitalizations (14.4%) and ECHO (27%), but the reduction in medical visits was higher in the PoC setting (38% compared to 2.5%), resulting in higher savings compared to Lab. Using NT-proBNP for CHF diagnosis in primary care could result in considerable costs savings for the public health system in Portugal. This evidence might support health policy makers to reconsider the resource management and define a new strategy to mitigate the impact of CHF. A insuficiência cardíaca crónica (ICC) é um problema de saúde pública crescente, mas o diagnóstico continua desafiante, nomeadamente nos cuidados de saúde primários. O objetivo deste estudo é avaliar e quantificar o impacto orçamental para o Serviço Nacional de Saúde (SNS) da introdução do NT-Probnp nos Cuidados de Saúde Primários para o diagnóstico de ICC. Foi efetuada uma análise de impacto orçamental para estimar a potencial economia de custos da utilização do NT-Probnp na avaliação inicial do doente com sintomas sugestivos de ICC, com o horizonte de um ano. Foram comparados três braços: cuidado padrão (cp) sem NT-Probnp; a utilização do biomarcador em point-of-care (poc) ou laboratório (lab). Foi usado um modelo de árvore de decisão para estimar os custos associados a cada um dos cenários. Foi estimado um total de 81 012 doentes com apresentação sugestiva de ICC. A utilização do NT-Probnp como meio diagnóstico primário pela medicina geral e familiar mostrou-se economizadora de custos, seja efetuado em lab ou POC, gerando uma economia anual estimada de 935.657€ e 2.982.443€, respetivamente. A economização de custos é devida à redução de consultas médicas, internamentos e ecografia (eco). A utilização de NT-Probnp em lab ou poc gera reduções idênticas em internamentos (14,4%) e eco (27%), mas a redução de consultas médicas é superior em poc (38% comparado com 2,5%), justificando a maior economia de custos neste contexto. A utilização de NT-probnp no diagnóstico de ICC nos Cuidados de Saúde Primários pode resultar numa redução de custos considerável para o SNS. Esta evidência pode suportar os decisores de política de saúde a reconsiderar a gestão de recursos e a definir uma nova estratégia para mitigar o impacto da doença.